Acquisition of family agriculture foods for school food according to brazilian regions: a review (Research, Society and Development, 2021)
Introduction: Law 11.947/2009 establishes that, at least, 30% of the total financial resources transferred under the National School Feeding Program (PNAE), should be used to purchase food from family farming and rural family enterprises. Objective: The present study provides an overview of the acquisition of food from family agriculture for the PNAE, by analyzing compliance with the minimum percentage required by law in the five regions of Brazil. Methodology: It is a literature review for the period from 2009 to 2019. For this purpose, thirty articles were selected from the Scielo, Spell and Pubmed databases. Results: There was acquisition of food for PNAE in all Brazilian regions. The South region has a higher prevalence of Executing Entities that applied resources below the stipulated percentage of 30% in 2011, 2013 and 2014. Paradoxically, this region has a higher prevalence of Executing Entities that have invested more than 30% of PNAE resources from family agriculture in the same period. Conclusion: The results show that municipalities and states have distinct difficulties in meeting the percentage required by law, and these are associated with the social, economic, cultural and environmental inequalities evident in each Brazilian region.